French Society and the Algerian Revolution (1954–1962) Translation of Kaninskaya Galina Nikolaevna’s article: French Society and the Algerian Revolution (1954–1962 - himmi, yakoub (The Algerian Historical Journal, 2026)
The article examines the reaction of French society to the Algerian War of 1954-1962, which was unleashed by the French governments of the Fourth Republic, which largely contributed to the fall of this republic. Having come to power on the wave of the rebellion of ultra-colonialists from Algeria, de Gaulle not only created and headed the new Fifth Republic, but also granted independence to Algeria. The positions of various political parties and their leaders, as well as ordinary citizens during the war are presented. The evolution of the views of French public opinion towards the recognition of the independence of the Algerian people is traced.